Can Deliberative Minipublics Influence Public Opinion? Theory and Experimental Evidence. (September 2018) - Ingham, Sean; Levin, Ines
Deliberative minipublics are small groups of citizens who deliberate together about a policy issue and convey their conclusions to decision makers. Theorists have argued that deliberative minipublics can give observers evidence about counterfactual, "enlightened" public opinion—what the people would think about an issue if they had the opportunity to deliberate with their fellow citizens. If the conclusions of a deliberative minipublic are received in this spirit and members of the public revise their opinions upon learning them, then deliberative minipublics could be a means of bringing actual public opinion into closer conformity with counterfactual, enlightened public opinion. We formalize a model of this theory and report the results of a survey experiment designed to test its predictions. The experiment produced evidence that learning the conclusions of a deliberative minipublic influenced respondents' policy opinions, bringing them into closer conformity with the opinions of the participants in the deliberative minipublic.